2013
DOI: 10.1016/j.engstruct.2013.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Smart monitoring of aeronautical composites plates based on electromechanical impedance measurements and artificial neural networks

Abstract: This paper presents a structural health monitoring (SHM) method for in situ damage detection and localization in carbon fiber reinforced plates (CFRPs). The detection is achieved using the electromechanical impedance (EMI) technique employing piezoelectric transducers as high-frequency modal sensors. Numerical simulations based on the finite element method are carried out so as to simulate more than a hundred damage scenarios. Damage metrics are then used to quantify and detect changes between the electromecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 37 publications
(45 reference statements)
1
43
0
Order By: Relevance
“…PZTs PNN SFAN FAN Kappa-PSO-FAN P1 PZT #1 96% 98% 98% 100% PZT #4 62% 82% 82% 84% P2 PZT #1 72% 82% 82% 86% PZT #2 68% 76% 76% 84% P3 PZT #3 80% 100% 100% 100% PZT #4 60% 84% 84% 84% P4 PZT #3 64% 40% 40% 60% PZT #4 78% 68% 68% 88% P5 PZT #3 48% 68% 68% 68% PZT #4 72% 70% 74% 75% Investigating the results presented in Table 4 , it can be observed that the PNN based method presented the worst performance by taking into account the success rate for identifying structural damage. It is important to mention that PNN based methods have been widely recurrent in the SHM literature ( De Oliveira & Inman, 2017;Na & Lee, 2013;Palomino et al, 2014;Selva et al, 2013 ). As observed, results for SFAN and FAN have presented practically the same performance for the overall success rate when working in the same conditions.…”
Section: Positionssupporting
confidence: 56%
See 1 more Smart Citation
“…PZTs PNN SFAN FAN Kappa-PSO-FAN P1 PZT #1 96% 98% 98% 100% PZT #4 62% 82% 82% 84% P2 PZT #1 72% 82% 82% 86% PZT #2 68% 76% 76% 84% P3 PZT #3 80% 100% 100% 100% PZT #4 60% 84% 84% 84% P4 PZT #3 64% 40% 40% 60% PZT #4 78% 68% 68% 88% P5 PZT #3 48% 68% 68% 68% PZT #4 72% 70% 74% 75% Investigating the results presented in Table 4 , it can be observed that the PNN based method presented the worst performance by taking into account the success rate for identifying structural damage. It is important to mention that PNN based methods have been widely recurrent in the SHM literature ( De Oliveira & Inman, 2017;Na & Lee, 2013;Palomino et al, 2014;Selva et al, 2013 ). As observed, results for SFAN and FAN have presented practically the same performance for the overall success rate when working in the same conditions.…”
Section: Positionssupporting
confidence: 56%
“…One reason for the increasing effort s in the related research is that those methods can be applied to different types of structures and several different damage scenarios. For example, methods based on PNN, applied to damage identification in SHM, are addressed in Na and Lee (2013), Palomino, Steffen, and Finzi Neto (2014) and Selva, Cherrier, Bundinger, Lachaud, and Morlierb (2013) . According to Na and Lee (2013) , methods based on PNN present a faster training procedure and they are easier to implement than the traditional Back-Propagation based methods.…”
Section: Introductionmentioning
confidence: 99%
“…Unstiffened composite shells are used in a wide range of critical engineering structures [1][2][3]. These shells are prone to buckling and are highly sensitive to imperfections which arise during the manufacturing process [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The neural network [10,11] is a potentially powerful algorithm because of the ability to learn from past experiences and memorize the patterns in the form of an associative memory, and the special attention has been drawn to damage recognition and classification. Li et al [12] presented a thorough investigation into a vibration-based damage identification method utilizing dimensionally reduced residual frequency response function data in combination with neural networks to identify locations and severities of damage in numerical and experimental beam structures.…”
Section: Introductionmentioning
confidence: 99%